The tragedy of the Ukrainian peasantry during the Holodomor times in the Diaspora prose (based on the works of Olena Zvychaina and Ivanna Chornobryvets) (Literatures of the World: Poetics, Mentality and Spirituality, 2017)
The article deals the works of Diasporaʼs writers Olena Ordinary and Ivanna Chornobryvets on the theme of the Holodomor of 1932–1933. It focuses on the specifics of the authorʼs vision of ethnocide, the means and techniques of psychological analysis of images, historical realities. The story tells about the existential existence of man in a totalitarian society, an expressionistic reflection of the tragedy of Ukrainians.
Keywords: holodomor; historical truth; documentary; existentialism; naturalism; psychologism